“Freely you have received, freely give”: A Socio-Ethical Analysis of Charismatic Engagements and Pentecostalism in Nigeria - Sunday Daniel AJAYI (Africajournals, 2022)
The manifestation and demonstration of spiritual gifts have always generated a lot of argument among Christians and non-Christians in Nigerian society. While some people deny the reality of the gifts thereby camping with the cessationists, other parties submit to the continuation of the spiritual gifts among the contemporary Christians. However, in scholarship the discourse has taken different dimensions which include the theological, effectual, biblical and philosophical perspectives with little attention paid to the socio-ethical aspect of the matter which is the major concern of this paper. The work is premised on Thomas Hobbes’ Theory of Psychological Egoism, which emphasises the benefit or reward as the motivating factor for every action performed by man, this article intends to investigate the alleged commercialization of prophetic gifts among the Nigerian pastors and to determine whether this is the major cause for the increase of the demonstration of charismatic gifts in the country. Interviews were conducted with Christians and ministers for data collection; which were complemented with relevant literature. The paper pays attention to charismatic display and Pentecostalism, current level of charismata in Nigerian Pentecostal churches, encouraging factors of charismatic activities and socio-ethical assessment of the display of spiritual gifts in Nigeria’s churches, while Christian morally pertinent ways of demonstrating spiritual gifts in an ethical manner is recommended